Corynebacteria from the respiratory microbiota modulate inflammatory responses and associate with a reduced pneumococcal burden in the lungs - Bergenfelz, Caroline; Do, Phuong; Larsson, Liv; Ivarsson, Hanna; Malmborn, Kasper; Håkansson, Anders P. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCertain species from the normal respiratory tract microbiota have recently been proposed to positively influence human health. Corynebacterium propinquum and C. pseudodiphtheriticum (Corynebacteria) are two Gram-positive species that frequently colonize the upper respiratory tract and strongly associate with a reduced incidence of respiratory tract infections. The specific role of Corynebacteria during respiratory health and disease is, however, largely uncharacterized.MethodRespiratory tract epithelial cells NCI-H292 and BALB/cByJ mice were inoculated with Corynebacteria (C. propinquum 2018M3 and 2019M4, and C. pseudodiphtheriticum 2019M8 and 2020M12) alone or with subsequent challenge with Streptococcus pneumoniae (pneumococci). The inflammatory response and the bacterial burden of both species over time were determined by Western blot, luciferase assay, cytokine bead array, flow cytometry and viable plate counts on blood agar plates.ResultsClinical isolates of Corynebacteria were well tolerated by human cells and mice. Corynebacteria induced a transient inflammatory response during healthy conditions in the absence of known pathogens. Pre-exposure or nasal priming with Corynebacteria did not affect subsequent acquisition of pneumococci but were associated with a modulated inflammatory response in vitro and in vivo as well as with a reduced pneumococcal burden in the respiratory tract of mice. This indicates that the presence of C. propinquum or C. pseudodiphtheriticum may protect against severe pneumococcal infections.ConclusionsIn this study, we delineate the role of Corynebacteria from the normal microbiota that epidemiologically associate with respiratory health. We show that the presence of Corynebacteria modulates the inflammatory response to pneumococci and associate with faster decrease in pneumococcal burden, primarily in the lower respiratory tract. Our data indicate that Corynebacteria has potential to protect against severe pneumococcal infections.